BSCI-11. STROMAL PLATELET DERIVED GROWTH FACTOR RECEPTOR-β (PDGFRβ) PROMOTES BREAST CANCER BRAIN METASTASIS. (12th August 2019) - Thies, Katie; Hammer, Anisha; Hildreth, Blake; Russell, Luke; Sizemore, Steven; Trimboli, Anthony; Kladney, Raleigh; Steck, Sarah; Das, Manjusri; Bolyard, Chelsea; Pilarski, Robert; Cuitino, Maria; et al.
Abstract: Stromal platelet-derived growth factor receptor-beta (PDGFRβ) has emerged as an actionable mediator of breast tumor-stromal communication. As a receptor tyrosine kinase, PDGFRβ is activated by its ligand, PDGFB, which is released by neighboring tumor epithelium and endothelium. However, how PDGF signaling mediates breast cancer (BC) initiation, progression, and metastasis remains unclear. To evaluate PDGFRβ in this disease, we developed a mouse model of stromal-specific PDGFRβ activation using the Fsp-cre transgene previously published by our group. Mesenchymal-specific activation of PDGFRβ promotes preferential experimental brain metastasis of PDGFB-expressing mammary tumor cells when injected intravenously and accelerates intracranial tumor growth of these cells. Mammary tumor cells expressing low levels of PDGFB do not exhibit a similar increase in brain metastases in PDGFRβ mutant mice. To our knowledge, this is the first example where genetic manipulation of the stroma leads to an increased incidence of BCBM. Our pre-clinical data suggests that primary breast tumors that express high PDGFB could preferentially metastasize to the brain. To test this in patients, we analyzed PDGFB protein expression in a tissue microarray comprised of HER2-positive and triple negative BC primary tumors. While high PDGFB did not correlate with site-independent metastatic recurrence, it was prognostic of brain metastasis, mirroring our mouse data. Our findings suggest that high primary tumor PDGFB expression defines a subset of BC patients predisposed to brain metastases. These patients may benefit from therapeutic intervention of PDGFRβ signaling. To test this pre-clinically, we treated mice harboring intracranial tumors with the PDGFR-specific inhibitor, crenolanib. Excitingly, crenolanib treatment significantly inhibited the brain tumor burden in these mice. Combined, our findings (1) advocate that primary tumor expression of PDGFB is a novel prognostic biomarker for the development of BCBM and (2) support clinical trial evaluation of PDGFR inhibitors for the prevention and treatment of BCBM.